Analisis Manfaat Ekonomi Tidak Langsung (Non-Market Value) Taman Matahari di Medan bagi Masyarakat - Khairani Mardatillah; Muhammad Sukri Ritonga; Fikri Mahesa Amin Purba; Widya Arlia; Sari Wulandari (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the indirect economic benefits (non-market value) of Taman Matahari in Medan for the surrounding community, focusing on its contribution to literacy activities and social interaction. Taman Matahari, located adjacent to Taman Bacaan Masyarakat (TBM) Al-Azhari Library, serves as a public space that supports the quality of life of the community. The research method used is qualitative, with data collection through interviews and direct observation. The results show that Taman Matahari provides a range of indirect economic benefits, including increased income for small traders, improved environmental quality, and strengthened social capital. Despite challenges in environmental awareness, the economic potential generated demonstrates the importance of sustainable park management. This research recommends strengthening management capacity, environmental education programs, and developing supporting facilities to optimize the park's benefits to the community.